ANALYZING THE PERFORMANCE OF SOUTH AFRICA’S COMMODITY MARKET PRICES THROUGH BUSINESS CYCLE INDICATORS - Chama CHIPETA (Studia Universitatis Babeş-Bolyai Negotia, 2022)
The soundness of the capital market is crucial in establishing resilient financial market deepening and general economic progress. Equally, the health of the financial market’s commodity market is undoubtedly a key determinant of inclusion, equitability, including sustained growth and development, especially in commodity-dependent countries. However, countries worldwide are faced with the continued challenge of falling commodity prices, presenting varied negative effects. Understanding the performance of the commodity market through lenses of fundamental or real-side indicators, other than just micro-specific financial or monetary variables, could prove helpful in constructing better inferences of the commodity market from an industrial, investor and policy standpoint. This study conducted a comprehensive evaluation of South Africa’s official component series of the business cycle indicators (BCI), to assess their potential and capacity to serve as explanatory signals for commodity market prices. The study utilized the cross-correlations tests, Granger causality tests, variance decomposition and charting techniques to assess the co-movement and concordance between business cycle component series (regressors) and the All-commodity index (regressand). Monthly observations from June 2003 to November 2017 were employed. Evidence of existing co-movement or concordance was established between the commodity market and most of the BCIs. Significant BCIs were identified as leading, lagging and coincident indicators for the commodity market based on the underlying properties established in the empirical estimates of the study.